FORSCHA SOʻZLAR TARKIBIDA QOʻLLANILGAN -AK AFFIKSI HAQIDA AYRIM MULOHAZALAR - Abdulhamid, Abduvaliyev (FILOLOGIYA UFQLARI JURNALI, 2021)
This article provides detailed information on the use of the affix -ak , meaning smallness, inferiority, deficiency of the vocabulary of the Uzbek language